Fluridone promotes the germination of Polygonatum cyrtonema seeds by modulating hormone signal transduction, phenylpropanoid biosynthesis, and energy metabolism - Xiaogang Jiang; Darong Li; Hua Wang; Yuying Yang; Kaidi Yu; Jinwen You; Haihua Liu; Xiaoliang Guo; Yinsheng He; Wuxian Zhou; Qingfang Wang (Chemical and Biological Technologies in Agriculture)
Abstract Polygonatum cyrtonema Hua functions as a highly valued medicinal herb. However, the seeds of P. cyrtonema exhibit morphophysiological dormancy. In this study, P. cyrtonema seeds were treated with a range of fluridone concentrations (0, 50, 100, 250 and 500 mg/L). The germination rate and radicle length were recorded on the 25th, 30th, 40th, 50th, and 60th days of the experiment. In addition, we investigated the metabolome and transcriptome differences in P. cyrtonema seed under fluridone treatments of 0 mg/L (CK), 50 mg/L (FL5), and 250 mg/L (FL20). The findings revealed that suitable fluridone significantly increased the germination rate and promoted radicle elongation of P. cyrtonema seeds. Furthermore, fluridone treatments significantly promoted the germination by reducing abscisic acid (ABA) content, while increasing the levels of auxin (IAA) and cytokinin (CTK). Most genes associated with IAA and CTK in FL5 and FL20 showed higher expression levels when compared with the control, whereas genes related to dormancy and senescence showed the opposite trend. Moreover, genes associated with phenylpropanoid biosynthesis exhibited significant upregulation in FL5 and FL20 when compared with the control, suggesting that fluridone might alleviate the abiotic stress and provide a more favorable environment for germination. In addition, genes associated with the starch and sucrose metabolism showed significant upregulation, contributing to the energy supply for the seed germination. In summary, this study identified 250 mg/L as the optimal fluridone concentration for promoting the germination of P. cyrtonema seed by regulating hormone-mediated signaling, starch/sucrose metabolism, and phenylpropanoid biosynthesis. The current research provides a theoretical basis and practical techniques for applying fluridone to release the dormancy and enhance germination of P. cyrtonema seeds. Graphical abstract